Relationships between organizational performance and change factors and manufacturing firms' leanness - Stone, Kyle Bradley, author; Chermack, Thomas J., advisor; Gilley, Jerry W., committee member; Kraiger, Kurt, 1957-, committee member; Makela, Carole J., committee member (Colorado State University. Libraries, 2010)
The purpose of this non-experimental research study was to examine relationships between organizational performance and change (OP&C) factors and the perceived leanness and objective performance measures within a medium-sized manufacturing organization engaged in lean transformation. Burke (2008) suggested successful transformational change is often predicated upon an organization's ability to understand dimensions influencing change interventions as outlined in the Burke-Litwin model of OP&C. To better understand why lean interventions succeed in some instances and not in others, it is important to study relationships between OP&C dimensions and their impact on the leanness an organization achieves. To investigate relationships between lean and the OP&C model, two instruments were used to gather perceptions of leanness and an overall assessment of 14 variables from the OP&C model. The Lean Organization Self Assessment Manufacturing Survey (LOSAMS) was administered to leaders of nine different plants within the same organization to determine a leanness score. The Burke-Litwin Organizational Assessment Survey (OAS) was administered to employees in same nine manufacturing plants gathering perceptions related to 14 factors of OP&C. While a number of statistical significant findings were found with small effect sizes among the LOSAMS and Burke-Litwin OAS variables, some statistical significant findings with much larger than typical effect sizes between LOSAMS scores and objective financial data were discovered. However, the reliability and validity of the LOSAMS is questionable rendering the implications of the findings weak. Other practical implications for this research study are many. The conceptual development of a Lean Transformation Model promoted the use of sound organizational development, organizational change, and human resource development principles and practices that could benefit the well intentioned but ill-informed change agent. A systematic literature review explores four decades of scholarly lean literature in an effort to present a reliable history and shared language for future researchers. Reliability and validity of the Burke-Litwin OAS confirmed consistency but the LOSAMS revealed a promising but weak measure of leanness. Conclusions and a research agenda for future studies in lean transformations are offered in the final section.
Keywords: Toyota Production System; organizational performance and change; lean transformation; lean thinking; lean manufacturing; Burke-Litwin OP&C; Lean manufacturing -- North America; Organizational change -- North America; Organizational effectiveness -- North America; Industrial efficiency -- North America